1996
DOI: 10.1021/jf950519s
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics, Fatty Acid Composition, and Lipoxygenase Activity of Crude Pumpkin and Melon Seed Oils

Abstract: Physicochemical characteristics and fatty acid composition of crude oil and lipoxygenase activity of six varieties of pumpkin and melon seeds were investigated. Data obtained for the iodine value, saponification number, and acid value compare well with those of other edible oils. The major fatty acid in total lipid was 18:2 (n = 6), representing 68.7% for Citrullus lanatus (Chinese), 65% for C. colocynthis, 63.7% for C. lanatus (Iranian), 62% for C. lanatus (Egyptian), 53% for Cucurbita moschata, and 43% for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
63
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 12 publications
17
63
4
Order By: Relevance
“…These results are well within the range reported for conventional vegetable oils [21]. All the properties of EMSO (except the HHV) generally were in agreement with previous studies [22][23][24].…”
Section: Physicochemical Properties Of Egusi Melon Seed Oilsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are well within the range reported for conventional vegetable oils [21]. All the properties of EMSO (except the HHV) generally were in agreement with previous studies [22][23][24].…”
Section: Physicochemical Properties Of Egusi Melon Seed Oilsupporting
confidence: 92%
“…It was found that EMSO composed of six fatty acids: palmitic, palmitoleic, stearic, oleic, linoleic and linolenic acids. The fatty acid composition of the EMSO was in close agreement with previous studies [22,23,25]. Of the six fatty acids, linoleic acid is the most prevalent with the value of 61.41%.…”
Section: Fatty Ester Compositionsupporting
confidence: 91%
“…The content of unsaponifiable matter in the seeds decreased slightly from 1.8% to 1.0%. The quantity of unsaponifiable matter in the mature seeds was higher than that shown in previous publications (Al-Khalifa, 1996).…”
Section: Changes In the Lipid Composition Of Pumpkin Seeds During Thecontrasting
confidence: 74%
“…The content of linoleic acid is higher than the other fatty acids and varies from 35.7% to 56.6% followed by oleic acid (14.8-38.1%), palmitic acid (10.7-16.4%) and stearic acid (4.7-11.1%) (Achu et al, 2006;Al-Khalifa, 1996;Kim et al, 2012).…”
Section: Fatty Acid Compositionmentioning
confidence: 97%
See 1 more Smart Citation